Procrastinación académica y motivación intrínseca en estudiantes de educación inicial Facultad de Ciencias de la Educación y Humanidades UNAP Iquitos 2024 - Rodriguez Tafur, Rosario Jandyra (2025)
The general objective of the study was to relate academic procrastination with intrinsic motivation in early education students, Faculty of Educational Sciences and Humanities UNAP, 2024; In the methodological aspect, we worked with the type of descriptive – quantitative research, with a correlational design with a transversal approach. The sample was 150 students from the initial education school, to whom an assessment scale to measure the academic procrastination variable and an intrinsic motivation test were administered as instruments. Regarding the result, it is observed that there is a Pearson correlation coefficient of rxy= 0.645, which indicates a moderate and positive correlation between both variables, that is, as academic procrastination increases, so does intrinsic motivation in the students. of initial education. It is concluded by indicating that there is a highly significant statistical relationship between academic procrastination and intrinsic motivation.